2003
DOI: 10.1080/110241598750004670
|View full text |Cite
|
Sign up to set email alerts
|

Severe sepsis in cardiac surgical patients

Abstract: We concluded that severe sepsis mainly developed in cardiac surgery patients with serious operative and postoperative complications and was associated with a longer stay in both ICU and hospital, and a higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 0 publications
6
32
1
8
Order By: Relevance
“…Leal-Noval et al [16] showed in their study, administration of blood derivatives, in particular red blood cells, was associated with a development of severe postoperative infections (pneumonia). In addition to a higher incidence of postoperative pneumonia, blood transfusion has also been shown to be associated with deep sternal wound infection [17] and severe sepsis [18]. In agreement with these findings we demonstrated blood transfusion to be associated with a higher risk of infectious complication.…”
Section: Discussionsupporting
confidence: 81%
“…Leal-Noval et al [16] showed in their study, administration of blood derivatives, in particular red blood cells, was associated with a development of severe postoperative infections (pneumonia). In addition to a higher incidence of postoperative pneumonia, blood transfusion has also been shown to be associated with deep sternal wound infection [17] and severe sepsis [18]. In agreement with these findings we demonstrated blood transfusion to be associated with a higher risk of infectious complication.…”
Section: Discussionsupporting
confidence: 81%
“…Po tego typu operacjach 10-20% pacjentów wymaga hospitalizacji na oddziałach intensywnej terapii, a u 2-50% chorych z tej grupy dochodzi do powikłań septycznych, często zagraża-jących życiu chorego [1]. W ostatnich latach śmiertelność po operacjach kardiochirurgicznych jest nadal wysoka.…”
Section: Wstępunclassified
“…W piśmiennictwie światowym śmiertelność u chorych, u któ-rych rozwinęła się ciężka sepsa, kształtuje się na poziomie 20-70% [1]. W badaniu własnym śmiertelność u pacjentów ze wstrząsem septycznym po operacjach kardiochirurgicznych wyniosła 66,6%, co potwierdza powyższe dane.…”
Section: Dyskusjaunclassified
See 2 more Smart Citations